Molecular Docking Study of IPBCC.08.610 Glucose Oxidase Mutant for Increasing Gluconic Acid Production - Shobiroh Nuur' Alimah; Tony Ibnu Sumaryada; Waras Nurcholis; Laksmi Ambarsari (Jurnal Kimia Sains dan Aplikasi, 2022)
Glucose oxidase (GOD) is an oxidoreductase enzyme that catalyzes the oxidation of glucose to gluconolactone and hydrogen peroxide. Then, gluconolactone will be hydrolyzed to gluconic acid. The wide application of gluconic acid in various industries has increased production demand. However, glucose concentrations higher than 40% (w/w) inhibited the conversion of glucose to gluconic acid due to a decrease in the oxygen solubility concentration at pH 6, 30℃, and 1 bar pressure. Therefore, decreasing the value of Km is predicted to reduce saturation and enhance gluconic acid production. This study aimed to analyze the interaction between the IPBCC.08.610 GOD mutant with β-D-Glucose in improving gluconic acid production by decreasing the Km value. Mutations were performed in silico using Chimera and then docked using AutoDock Vina. The mutations resulted in distinct ligand poses in the binding pocket, different -OH conformations of the ligands, and changes in the T554M/D578P mutant’s hydrophobicity index (554 mutated from threonine to methionine, and 578 mutated from aspartate to proline), and decreased ΔG and Km values in the H559D mutant (559 mutated from histidine to aspartate), D578P and T554M/D578P. This decrease might strengthen the ligand-receptor interaction, increasing gluconic acid production. The H559D was the best mutant to increase production based on the ΔG, Km value, and stability due to the addition of hydrogen bonds.